2005
DOI: 10.1159/000090336
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and Leptin Elevation in Postoperative Intra-Abdominal Sepsis

Abstract: Background: Both ghrelin and leptin are important signals in the regulation of food intake and energy balance. Leptin concentrations are elevated in the majority of obese individuals, and its levels usually correlate with adiposity and body mass index. Ghrelin as a new growth hormone (GH)-releasing peptide was discovered in 1999. Ghrelin stimulates food intake and exhibits gastroprotective properties. Many other regulatory effects of both ghrelin and leptin involving cardiovascular, gastrointestinal, renal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 44 publications
2
33
0
1
Order By: Relevance
“…The response of ghrelin Ϫ/Ϫ mice to endotoxin would answer the question whether ghrelin is a key regulator or just a by-player in the complicated immuno-neuroendocrine mechanisms. Ghrelin was found to be significantly elevated in 25 surgical patients with postoperative intraabdominal sepsis (32), but more studies and a better profiling of ghrelin fluctuations in acute infections are needed before testing its possible therapeutic effect in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The response of ghrelin Ϫ/Ϫ mice to endotoxin would answer the question whether ghrelin is a key regulator or just a by-player in the complicated immuno-neuroendocrine mechanisms. Ghrelin was found to be significantly elevated in 25 surgical patients with postoperative intraabdominal sepsis (32), but more studies and a better profiling of ghrelin fluctuations in acute infections are needed before testing its possible therapeutic effect in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ankylosing spondylitis that is characterized by a chronic inflammation of the spine [130], and septic patients were reported to have high serum concentrations of ghrelin [131]. The increase in serum ghrelin was also reported in animal models: serum ghrelin concentrations were higher in rats with cerulein-induced severe pancreatitis [132] and those with adjuvant-induced arthritis [133], and in mice with trinitrobenzene sulfate-induced acute colitis [134].…”
Section: Serum Ghrelin Levels In Inflammationmentioning
confidence: 95%
“…Several studies, both in animal models and humans, have demonstrated that sepsis modulates plasmatic ghrelin concentrations and that the administration of ghrelin has beneficial effects on sepsis. In surgical patients with postoperative intraabdominal sepsis plasma levels of ghrelin increased and positively correlated with TNF-a and IL-6 levels (Maruna et al 2005). In healthy human subjects, LPS administration induced a biphasic change in circulating ghrelin levels, with a rapid increase reaching the maximum after the pick of TNF-a and a subsequent decrease with the nadir 5 h after LPS administration (Vila et al 2007).…”
Section: Cachexiamentioning
confidence: 96%